POTRET PERTUMBUHAN KUNJUNGAN WISATAWAN DALAM PERSPEKTIF ISLAM DI KABUPATEN BANYUWANGI - Jauhariyah, Nur Anim; Habibulloh, Habibulloh; Yazid, Azy Athoillah (Jurnal Ekonomi Syariah Darussalam, 2021)
Tourism potential is a sector that has an important role in continuing the economic journey in a region. The tourism sector is a promising source of income to be further managed in an effort to increase income. The purpose of this study was to determine the growth of tourist visits in Banyuwangi Regency. The data used are secondary time series data using descriptive statistical analysis to determine the growth of tourist visits in Banyuwangi Regency. The results showed that growth in 2018 the growth in the number of tourist visits experienced a lowest point of 0.080%, while the highest growth was in 2016, which was 1.078%.